Development of the Together - Teens&20s microsite, an online resource for adolescent and young adult cancer patients - Sarah Daniels; Elizabeth Bartholomew; Heather Chambliss (Elsevier, 2023)
Objectives: The purpose of this study was to explore the information needs and preferences of adolescent and young adult (AYA) cancer patients to guide next steps for development of a new online resource for this audience. The goals were to understand information needs, prioritize topic areas, and inform website design and functionality. Methods: Participants were AYA cancer patients ages 13-25 years. We used multiple methods in two phases to gather audience feedback. The first phase collected quantitative data in an electronic survey (n = 45) about AYA patients' internet use and content preferences. The second phase collected qualitative data through focus groups (n = 13) about user preferences for content design and website function. Results: Survey results showed AYA patients were more interested in content about how treatments would impact their lives rather than the treatments themselves. They preferred content on school, careers, relationships, independence, side effects, and fertility. The focus groups indicated AYA patients prefer a clean, stylish design; infographics and visual aids; and the ability to find information quickly and control the amount they read. Conclusions: Online resources represent an important opportunity to advance cancer education for AYA patients. However, it is important to consider the information needs and preferences of this audience in content design and delivery. Innovation: Practitioners should use stakeholder input to guide the creation of patient education resources that are age- and audience-appropriate. This study provides insights into AYA information needs and preferences in pediatric oncology.